Comment on "Asynchronous variation in the East Asian winter monsoon during the Holocene" by Xiaojian Zhang, Liya Jin, and Na Li. Issue 4 (16th February 2016) - Rashid, Harunur; Marche, Brittany; Vermooten, Marli; Parry, Devon; Webb, Michaela; Brockway, Brent; Langer, Keesha
Abstract: Comparing paleoproxy records throughout China and two climate models simulation results, Zhang et al. (2015) reported asynchronous Holocene spatiotemporal decline of the East Asian winter monsoon. Six sea surface temperature (SST) proxy records from the Atlantic Ocean and northern Indian Ocean and South China Sea were used to validate climate simulations results. However, the referred Mg/Ca SST record from the western Atlantic Ocean is simply nonexistent and the northeast Atlantic Mg/Ca SST data do not reflect winter SST as Zhang et al. (2015) argued to support the driving mechanisms. Furthermore, the western Indian Ocean SSTs data used in Zhang et al. (2015) do not reflect the winter SSTs or regional changes in the Holocene SSTs. Therefore, we question the validity of model simulation results and hence the reliability of conclusions in Zhang et al. (2015).